2002
DOI: 10.1046/j.1526-0968.2002.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Endotoxin by Beta2‐Microglobulin Adsorbent Column (Lixelle): The New Approach for Endotoxinemia

Abstract: We previously reported that Lixelle, which was used for beta 2 -microglobulin (BMG) adsorption columns, could adsorb not only BMG but also inflammatory cytokines. We became interested in the application of Lixelle for patients with endotoxinemia and researched its ability to adsorb microorganism components in vitro using lipopolysaccharide (LPS) (Escherichia coli B8), endotoxin (ET) contaiminated water. The initial concentrations of each water solution were LPS (ET 29,135 EU/L) and contaminated water (ET 3,523… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The positive end‐expiratory pressure (PEEP) was set at 5–10 cm H 2 O, unless the blood pressure was <80 mm Hg. The pressure support (PS) was set to maintain 10 cm H 2 O unless the airway pressure was >45 cm H 2 O at end of inspiration, and the ventilation rate was set to 16–25 breaths/minute (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive end‐expiratory pressure (PEEP) was set at 5–10 cm H 2 O, unless the blood pressure was <80 mm Hg. The pressure support (PS) was set to maintain 10 cm H 2 O unless the airway pressure was >45 cm H 2 O at end of inspiration, and the ventilation rate was set to 16–25 breaths/minute (10).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that β2‐microglobulin adsorption direct hemoperfusion column, Lixelle, adsorbs endotoxins and cytokines more efficiently than a PMX column does. Lixelle was also reported to be applied in a direct hemoperfusion system for systemic inflammatory response syndrome (SIRS) patients and was shown to be capable of treating hypercytokinemia (9,10). It is therefore suggested that Lixelle–DHP is an alternative therapy for ARDS/ALI in place of PMX–DHP.…”
mentioning
confidence: 99%
“…In recent years, adsorbent matrices that are based on hydrophobic interaction and size exclusion (Lixelle ; Kaneka Co., Ltd., Tokyo, Japan and Betasorb ; Renaltech International LLC, New York, NY, USA) have been developed for the extracorporeal removal of b 2 -m [6,7]. However, their specificity and/or affinity for b 2 -m remains in question, complicating the evaluation of patient outcome due to their use [8][9][10].The ideal technology for the extracorporeal removal of b 2 -m should be highly specific, so as to prevent the significant loss of proteins and other molecules that are beneficial to the patient. A highly specific b 2 -m removal system could also serve as a valuable tool for research.…”
mentioning
confidence: 99%
“…This device consists of a porous cellulose bead modifi ed with a hydrophobic ligand that is used to target ␤ 2 m. A symptomatic improvement was seen in patients suffering from DRA when this device was used in series with high-fl ux dialysis membranes, such as polyacrylonitrile (AN69) and PMMA. Although the plasma concentrations of ␤ 2 m were reduced by up to 70%, a decrease in blood pressure and hematocrit of the patients treated with this device was observed [13,14] . MedaSorb Technologies, LLC, New York, N.Y., USA, developed another adsorbent column called BetaSorb TM .…”
mentioning
confidence: 96%
“…An adsorbent column, referred to as Lixelle [10,[12][13][14][15] is in use in Japan for the selective elimination of ␤ 2 m from the blood of patients with DRA. The specifi city and/ or affi nity of this matrix for ␤ 2 m is in question since it also removes other middle molecular weight molecules such as infl ammatory cytokines [13,14,26,27] . This device consists of a porous cellulose bead modifi ed with a hydrophobic ligand that is used to target ␤ 2 m. A symptomatic improvement was seen in patients suffering from DRA when this device was used in series with high-fl ux dialysis membranes, such as polyacrylonitrile (AN69) and PMMA.…”
mentioning
confidence: 99%